Exploring Loneliness and Alienation in The Sound Inside by Adam Rapp (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Adam Rapp's The Sound Inside (2019) is an extremely introspective and unsettling play that investigates loneliness, solitude, and human attachment. The critique examines how Rapp's play addresses the psychological and existential issues of individuals in modern society, with focus on protagonist Bella Baird, a Yale professor, as she becomes obsessively close but enigmatic with her student, Christopher. The research question is an analysis of how Rapp's play represents loneliness and alienation as existential conditions rather than emotional conditions. The research seeks to analyze the characterizations and narrative techniques which represent isolation, to debate the role of literature and narrative as a coping strategy, and to analyze the broader social consequences of disconnection and loneliness in contemporary life. The study employs existentialist literary theory and draws particular reference to the work of Jean-Paul Sartre and Albert Camus in order to recognize loneliness and alienation as the underlying facts of human existence. The thesis is developed that Bella's alienation is not merely the product of personal trauma, but symptomatic of the isolation of the intellectual and emotional environments of the modern era. The lean production and non-linear design of the play are part of the project of presenting loneliness, and the rapport between Bella and Christopher demonstrate the fragility of human connection. The Sound Inside ultimately presents loneliness as a condition of human being, forcing audiences to engage with the contradiction of desiring to be connected without vulnerability. This study contributes to the growing body of work on existentialist themes in new American drama, showing how Rapp's play mirrors broader social anxieties regarding isolation and meaning.